Living Benthic Foraminifera from the Surface and Subsurface Sediment Layers Applied to the Environmental Characterization of the Brazilian Continental Slope (SW Atlantic) - de Carvalho Santa Rosa, Luciana Cristina (2021)
Living benthic foraminifera (>63 µm) were studied to characterize the continental slope of the Potiguar Basin (SW Atlantic). Foraminifers from the surface (0–2 cm), subsurface (2–5 cm), and integrated (0–5 cm) sediment layers were analyzed to verify their contribution to environmental characterization. It was also estimated if and which changes occur when the subsurface is added. Sampling stations were distributed in five transects in four isobaths (150, 400, 1000, and 2000 m). Sediment samples were fixed with 4% buffered formaldehyde and stained with Bengal rose. Were recorded 396 species in the surface layer, 228 in the subsurface, and 449 in integrating both layers. This study did not include tubular agglutinated species. The assemblages from 150 m isobath indicated the upper slope, from 400 m indicated the middle slope and the ones from the 2000 m indicated the lower slope. The surface layer’s assemblage at 1000 m isobath was more similar to the middle slope; in contrast, its subsurface layer’s assemblage had more similarity with the lower slope. Rarefaction curves, Permanova, and NMDS routines indicated a high resemblance between surface and integrated layers. Therefore, the first two centimeters were sufficient to characterize this region based on living benthic foraminifera.